Magnetically-propelled fecal surrogates for modeling the impact of solid-induced shear forces on primary colonic epithelial cells. (September 2021) - Hinman, Samuel S.; Huling, Jennifer; Wang, Yuli; Wang, Hao; Bretherton, Ross C.; DeForest, Cole A.; Allbritton, Nancy L.
Abstract: The colonic epithelium is continuously exposed to an array of biological and mechanical stimuli as its luminal contents are guided over the epithelial surface through regulated smooth muscle contraction. In this report, the propulsion of solid fecal contents over the colonic epithelium is recapitulated through noninvasive actuation of magnetic agarose hydrogels over primary intestinal epithelial cultures, in contrast to the vast majority of platforms that apply shear forces through liquid microflow. Software-controlled magnetic stepper motors enable experimental control over the frequency and velocity of these events to match in vivo propulsive contractions, while the integration of standardized well plate spacing facilitates rapid integration into existing assay pipelines. The application of these solid-induced shear forces did not deleteriously affect cell monolayer surface coverage, viability, or transepithelial electrical resistance unless the device parameters were raised to a 50× greater contraction frequency and 4× greater fecal velocity than those observed in healthy humans. At a frequency and velocity that is consistent with average human colonic motility, differentiation of the epithelial cells into absorptive and goblet cell phenotypes was not affected. Protein secretion was modulated with a two-fold increase in luminal mucin-2 secretion and a significant reduction in basal interleukin-8 secretion. F-actin, zonula occludens-1, and E-cadherin were each present in their proper basolateral locations, similar to those of static control cultures. While cellular height was unaffected by magnetic agarose propulsion, several alterations in lateral morphology were observed including decreased circularity and compactness, and an increase in major axis length, which align with surface epithelial cell morphologies observed in vivo and may represent early markers of luminal exfoliation. This platform will be of widespread utility for the investigation of fecal propulsive forces on intestinal physiology, shedding light on how the colonic epithelium responds to mechanical cues. Highlights: Magnetic nanoparticle-embedded agarose hydrogels were developed as surrogates for human feces. Software-controlled magnetic motors enable programmable studies of colonic motility. Propulsive shear forces were optimized for primary cell viability, surface coverage, and electrical resistance. Mucus production and cytokine secretion were modulated by magnetic agarose propulsion. Structural and cytoskeletal proteins remain properly distributed with alterations in lateral cell morphology.